A Type II Hybrid ARQ Protocol with Adaptive Modulation and Coding for Time-Correlated Fading Channels: Analysis and Design - Harsini, Jalil S; Lahouti, Farshad; Levorato, Marco; Zorzi, Michele (2010 IEEE International Conference on Communications, 2010)
This paper presents performance analysis and cross-layer design approaches for hybrid ARQ (HARQ) protocol in wireless networks which employ adaptive modulation and coding (AMC) at the physical layer and are subject to time-correlated fading channels. Utilizing a Markov channel model which accounts for the temporal correlation in successive parity transmissions by the adaptive rate HARQ protocol, we derive the system throughput and the packet loss probability based on a rate compatible punctured convolutional (RCPC) code family. As an application, we then present a cross-layer AMC design which takes into account the performance gain of the HARQ protocol at the link layer. The results illustrate that including AMC in the HARQ protocol leads to a substantial throughput gain, but the channel correlation strongly diminishes the performance of the HARQ protocol in terms of throughput and packet loss rate.